2012
DOI: 10.1039/c1ib00108f
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of intracellularATP provide new insight into the regulation of glycolysis in the yeast Saccharomyces cerevisiae

Abstract: Glycolysis in the yeast Saccharomyces cerevisiae exhibits temporal oscillation under anaerobic or semianaerobic conditions. Previous evidence indicated that at least two membrane-bound ATPases, the mitochondrial F(0)F(1) ATPase and the plasma membrane P-type ATPase (Pma1p), were important in regulating the glycolytic oscillation. Measurements of intracellular ATP provide a unique tool to understand the role of these membrane ATPases and how their activities are regulated. We have constructed a new nanobiosenso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 35 publications
6
34
0
Order By: Relevance
“…First, it was observed that the mitochondrial membrane potential (Δψ m ) oscillates with the same frequency as NADH. Next, it was found that mitochondrial F 1 F 0 ATPase activity seems to be important for the oscillations to take place . This experimental evidence for the participation of ATPase activity in the regulation of glycolytic oscillations is supported by studies of models of the pathway .…”
Section: Introductionmentioning
confidence: 74%
“…First, it was observed that the mitochondrial membrane potential (Δψ m ) oscillates with the same frequency as NADH. Next, it was found that mitochondrial F 1 F 0 ATPase activity seems to be important for the oscillations to take place . This experimental evidence for the participation of ATPase activity in the regulation of glycolytic oscillations is supported by studies of models of the pathway .…”
Section: Introductionmentioning
confidence: 74%
“…However, concentrations of ATP can also be high in starved cells and start to decrease when glycolysis is induced. In the absence of glucose, ATPase activity is switched off and the intracellular ATP concentration is high (Ytting et al ., ). The accumulation of adenosine triphosphate in the cell results in inhibition of phosphofructokinase (PFK), one of the main enzymes that regulate glycolysis (Bai et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Recently, Kloster and Olsen [62] investigated the role of intracellular ATPase activity using specific inhibitors for the three types of ATPases, namely F 0 F 1 ATPase, Pma1 and vacuolar ATPase, and showed that both inhibiting and stimulating ATPase activity suppress glycolytic oscillations. Further support of the role of ATPase in glycolytic oscillations comes from the recent study of Ytting et al (2012) [63]. However, the latter study uses a GAL1 promoter replacement pma1 mutant and does not present data for its isogenic wild type parental strain.…”
Section: Discussionmentioning
confidence: 99%